Long-term follow-up of repair-like replacement of mitral valve using autologous pericardiumCentral MessagePerspective - Tomoki Shimokawa, MD; Hitoshi Kasegawa, MD; Minoru Tabata, MD, MPH; Toshihiro Fukui, MD; Hajime Kin, MD; Atsushi Shimizu, MD; Tomoya Uchimuro, MD; Kenta Zaikokuji, MD; Schuichiro Takanashi, MD (JTCVS Techniques)
Objectives: The present study assessed the late results of the operation, which consisted of the construction of a stentless mitral valve using autologous pericardium and valve implantation. Methods: Between 2011 and 2018, among 1617 consecutive patients who underwent mitral valve operation at our institution, 15 adult patients (0.9%) with unrepairable mitral valves who wished to avoid conventional mitral valve replacement underwent this operation. Ten patients (67%) had a history of valve repair. After discharge, patients were prospectively followed-up with a echocardiographic evaluation up to the end point. The mean follow-up term was 70.8 ± 42.5 months. Results: There were no hospital deaths or thromboembolic events and only 1 late noncardiac death. Intraoperative transesophageal echocardiography of all patients revealed no or trivial mitral regurgitation. Eight patients (53.3%) underwent redo valve replacement within 12 years. Except 1 late death, the postoperative course was divided into 3 groups depending on the occurrence of redo surgery, as follows: an early reoperation group (reoperation within 4 years; n = 4), a late reoperation group (reoperation after 4 years; n = 4), and a free from reoperation group (n = 6). The latest transthoracic echocardiographic examination performed 7.2 ± 2.9 years after the operation revealed the grade of mitral regurgitation to be none in 2 patients, mild in 2 patients, mild to moderate in 1 patients, and moderate in 1 patient in the free from reoperation group. Conclusions: Despite the high incidence of reoperation, Normo operation can be a viable option during valve replacement, especially for young patients.